2016
DOI: 10.3945/jn.115.219238
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Supplementation of Green Tea Extract Does Not Modify Adiposity or Bone Mineral Density in a Randomized Trial of Overweight and Obese Postmenopausal Women

Abstract: Decaffeinated GTE was not associated with overall reductions in adiposity or improvements in BMD in overweight/obese postmenopausal women. However, GTE may be beneficial for reduction in tissue and gynoid %fat in individuals with higher BMI. This clinical trial was registered at www.clinicaltrials.gov as NCT00917735.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 54 publications
(53 reference statements)
1
50
0
4
Order By: Relevance
“…Since the completion of this meta-analysis, additional RCTs investigating the effects of tea or cocoa products containing flavanols on lipid and anthropometric variables have been added to the existing literature [111,169,170,171,172,173,174,175,176,177,178,179,180,181,182,183]. The heterogeneity of these trials remains high with population samples including mixed sexes and ages, obese, overweight, healthy, hyperlipidemic and/or diabetic subjects, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the completion of this meta-analysis, additional RCTs investigating the effects of tea or cocoa products containing flavanols on lipid and anthropometric variables have been added to the existing literature [111,169,170,171,172,173,174,175,176,177,178,179,180,181,182,183]. The heterogeneity of these trials remains high with population samples including mixed sexes and ages, obese, overweight, healthy, hyperlipidemic and/or diabetic subjects, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Others show no significant effects on these variables [175]. Noteworthy, some of these trials included stratification analyses by baseline conditions, medication, disease, age, sex, or even genotype and further point to specific responses in some subgroups [169,172,174,176,179]. Likewise, the intake of a cocoa product caused a greater increased of HDL in normocholesterolemic patients than in dyslipidemic patients [176], green tea capsules caused a significant reduction of total-cholesterol in women with a cholesterol baseline value above 5.17 mmol/L [169] or of LDL-cholesterol in patients not receiving anti-hyperlipidemic drugs [179].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] The above 2 studies, which were not adjusted, were inconsistent with our series. Besides, a prospective randomized controlled study also found no correlation between tea and BMD, [43] the main reason likely being the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome measures included body mass index; total fat mass; percentage of body fat; BMD; and circulating leptin, ghrelin, adiponectin, and insulin 68. Green tea extract may be beneficial in reducing tissue and gynoid percentage fat in individuals with higher body mass index, but there were no changes in any circulating parameters 68.…”
Section: Human Clinical Trialsmentioning
confidence: 99%